Volume 7: Ocean Engineering 2015
DOI: 10.1115/omae2015-41912
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Ship Manoeuvring in Shallow Water Through Free-Running Tests

Abstract: The shallow water effect on ship manoeuvring cannot be neglected. Most sea-going ships become more course stable when they sail from deep to (very) shallow water. International collaborations such as SIMMAN intend to grade up the knowledge on ship manoeuvring prediction through model tests and system based and numerical methods. Free-running model tests executed with the very large crude carrier KVLCC2 at two laboratories have been compared with the results of simulated turning circles and zigzag manoeuvres fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Besides the ship speed, Eloot and Vantorre (2011) investigated the influence of bank slopes on bank effect. In this research, a towing tank was used, and the results showed that if ships sail above the slope, sloped banks generate greater force than vertical banks and thus present a greater risk to safety of navigation.…”
Section: Bank Effectmentioning
confidence: 99%
“…Besides the ship speed, Eloot and Vantorre (2011) investigated the influence of bank slopes on bank effect. In this research, a towing tank was used, and the results showed that if ships sail above the slope, sloped banks generate greater force than vertical banks and thus present a greater risk to safety of navigation.…”
Section: Bank Effectmentioning
confidence: 99%
“…Ship waves in shallow water were addressed by Chen (1999) and Jiang (2003). Manoeuvrability analyses of ships in shallow water were presented by Eloot et al (2015) and Tonelli and Quadvlieg (2015). Gronarz (1997) and Mucha (2017) focused on the mathematical modelling of manoeuvring in shallow water.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of research teams throughout the world are advocating for a change in approach to the evaluation of simulation models (US Coast Guard, 1998; Fang et al, 2012). Berg and Ringen (2011) and Elot et al (2015) raised the point that the methods for validating numerical models used in manoeuvring simulators need to be improved.…”
Section: Introductionmentioning
confidence: 99%